Analisa Ketidaksesuaian Hasil Audit Management Mutu ISO 9001-2008 - ., Supriyati .; Wiyatno, Tri Ngudi (JURNAL TEKNIK INDUSTRI, 2021)
ISO is an international standard organization that is implemented in almost all institutions/organizations/companies, both for profit and non-profit organizations. In manufacturing companies and ISO services are one of the customer requirements. In doing work, ISO 9001 becomes a guide in carrying out all activities. Every activity that is carried out is based on procedures that have been made and standardized. To monitor the implementation of ISO 9001, internal and external audits are required. In an audit, if the activity is carried out not according to the procedure, there is a deviation/non-conformance and becomes a finding. The results of an internal audit at a company that implemented ISO 9001 2008 showed a decrease in percentage when compared to the previous period in four departments. Meanwhile, the results of the external audit/certification body found four findings in three departments, namely the control clause and the improvement clause. The final results of internal and external audits with several types of clauses can be concluded that the discrepancies found during the audit of the implementation of the ISO 9001 quality management system have not fully run according to the standards. The procedures that have been established have not been consistently carried out, control and responsibility weak handling.